Navigating the Complexities of HIV Prevention for Adolescents and Young Persons: A Science-to-Program and Systems Approach. - Dzinamarira, Tafadzwa; Moyo, Enos; Murewanhema, Grant (Adolescents (2673-7051), 2025)
This opinion paper dives into the crucial but challenging space of HIV prevention for adolescents and young persons (AYPs). While their vulnerabilities may be heightened, so too is their potential for resilience, innovation, and positive change. To safeguard their health and empower them to make informed choices, a comprehensive science-to-program and systems approach to HIV prevention is paramount. Recognizing their unique vulnerabilities and immense potential, these authors advocate for a multifaceted approach that bridges the gap between scientific evidence and program implementation within a robust healthcare system. This opinion unpacks how leadership, governance, health policies, human resources, health information systems, and HIV surveillance can be strengthened to create a supportive ecosystem where AYPs have the knowledge, resources, and services they need to thrive. This collective effort, involving policymakers, healthcare providers, educators, and AYPs themselves, is critical to a future where no young person is left behind in the fight against HIV.